First chemoenzymatic synthesis of immunomodulating macrolactam pimecrolimus - P. Ferraboschi; D. Colombo; M. De Mieri; P. Grisenti (Tetrahedron Letters, 2009)
The preparation of pimecrolimus, a synthetic derivative of ascomycin endowed with immunomodulatory activity, requires the selective protection of 24-hydroxy group of the ascomycin, before elaboration of the 32 one. The aim was achieved by means of two regioselective Candida antarctica lipase-catalyzed steps. The structure of the new key intermediates, 24-, 32-monoacetates and 24,32-diacetate, was established by means of an unambiguous NMR study.